Women Activists Challenges and Gender Issues: A Field Study in Iraq) - Dunya Salahdin Mirdan (QALAAI ZANIST JOURNAL, 2022)
Women activists in Iraq, who work on gender issues and women’s issues, face many obstacles and challenges. In this study, we try to identify these challenges and explain the reasons that hinder the work of women activists. Moreover, highlighting and identifying the factors that suspension the continuation of advocacy campaigns for women’s issues among women’s organizations. For this purpose, a qualitative method was used to interview 22 female activists of civil society organizations working on women’s issues and gender in their programs.